1990
DOI: 10.1002/sia.740160169
|View full text |Cite
|
Sign up to set email alerts
|

AES depth profiling of passive overlayers formed on nickel alloys

Abstract: Depth profiling analysis of passive films grown on the surface of two nickel-based alloys (Inconel 600 and Hastelloy C4) in NaCl media was carried out using Auger electron spectroscopy (Am) aod ioo sputtering. Improvement to the sequeotid sputtering model of HofmaM (1976) should be performed when preferential sputtering occurs, especially in Mwxmtaining alloys. In this way, the kinetic model of preferential sputtering of Ho et ul. (1976) was extended to the case of ternary alloys. However, concentration gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…This can be explained by preferential sputtering of Ni and Cr as also observed by Lorang et al for Hastelloy C4 and Mischler et al for Fe-Cr-Mo alloys. [21,23] However, previous work has also demonstrated that the kinetic order of dissolution is Mo<Ni<Cr at −0.46 V and Mo∼Cr Ni at −0.21 V in this particular ammoniacal test solution. [6] The surface layer enrichment in Mo may also be explained from this perspective.…”
Section: Potentiostatic Polarization Experimentsmentioning
confidence: 87%
See 4 more Smart Citations
“…This can be explained by preferential sputtering of Ni and Cr as also observed by Lorang et al for Hastelloy C4 and Mischler et al for Fe-Cr-Mo alloys. [21,23] However, previous work has also demonstrated that the kinetic order of dissolution is Mo<Ni<Cr at −0.46 V and Mo∼Cr Ni at −0.21 V in this particular ammoniacal test solution. [6] The surface layer enrichment in Mo may also be explained from this perspective.…”
Section: Potentiostatic Polarization Experimentsmentioning
confidence: 87%
“…The carbon intensity measured on the Hastelloy C4 was negligible within www.interscience.wiley.com/journal/sia approximately 25 monolayers or 6 nm of the surface. [21] Assuming similar contamination on alloy 625 we could approximate 6 nm of depth penetration after 360 s in our work (Fig. 6).…”
Section: Potentiostatic Polarization Experimentsmentioning
confidence: 95%
See 3 more Smart Citations